Maintaining quality of life in patients with chronic obstructive pulmonary disease (COPD) by extending the maintenance phase of community-based pulmonary rehabilitation: protocol for a randomised controlled trial (ComEx3 Study) - Lopez, Derrick (BMJ Open Respir Res, 2020)
INTRODUCTION: Pulmonary rehabilitation is a core component of the treatment of people with chronic obstructive pulmonary disease (COPD); however, the benefits gained diminish in the ensuing months. The optimal strategy for maintaining the benefits is unclear with weekly supervised maintenance exercise programmes proposed as one strategy. However, the long-term future of maintenance programs is dependent on quality evidence. METHODS AND ANALYSIS: The ComEx3 randomised controlled trial will investigate the efficacy of extending a weekly supervised maintenance programme for an additional 6 months following an initial 10-week maintenance programme (intervention) by comparing with a control group who receive the same 10-week maintenance programme followed by 6 months of usual care. 120 participants with COPD will be recruited. Primary objective is to determine health-related quality of life over 12 months. Secondary objectives are to determine functional exercise capacity trajectory and to perform an economic evaluation of the intervention to the health system. Outcomes will be analysed for superiority according to intention-to-treat and per-protocol approaches. ETHICS AND DISSEMINATION: Approval has been received from the relevant ethics committees. Findings will be disseminated in peer-reviewed journals and conferences, targeting those involved in managing people with COPD as well as those who develop policies and guidelines. CLINICAL TRIAL REGISTRATION: ANZCTR 12618000933257